Visioning a food system for an equitable transition towards sustainable diets—a South African perspective - Sobratee, N.; Davids, R.; Chinzila, C. B.; Mabhaudhi, Tafadzwanashe; Scheelbeek, P.; Modi, Albert Thembinkosi; Dangour, Alan D.; Slotow, R. (MDPI, 2022)
The global goal to end hunger requires the interpretation of problems and change across multiple domains to create the scope for collaboration, learning, and impactful research. We facilitated a workshop aimed at understanding how stakeholders problematize sustainable diet transition (SDT) among a previously marginalized social group. Using the systems thinking approach, three sub-systems, namely access to dietary diversity, sustainable beneficiation of natural capital, and ‘food choice for well-being’, highlighted the main forces governing the current context, and future interventions of the project. Moreover, when viewed as co-evolving processes within the multi-level perspective, our identified microlevel leverage points—multi-faceted literacy, youth empowerment, deliberative policymaking, and promotion of sustainable diet aspirations—can be linked and developed through existing national macro-level strategies. Thus, co-designing to problematize transformational SDT, centered on an interdisciplinary outlook and informational governance, could streamline research implementation outcomes to re-structure socio-technical sectors and reconnect people to nature-based solutions. Such legitimate aspirations could be relevant in countries bearing complex socio-political legacies and bridge the local–global goals coherently. This work provides a collaborative framework required to develop impact-driven activities needed to inform evidence-based policies on sustainable diets.